2020
DOI: 10.3390/atmos11080881
|View full text |Cite
|
Sign up to set email alerts
|

Space-Borne Monitoring of NOx Emissions from Cement Kilns in South Korea

Abstract: Nitrogen oxide (NOx) emissions from the South Korean cement industry are investigated with remote-sensing measurements, surface observations, and in situ aircraft measurements. In the Yeongwol, Danyang, and Jecheon regions of central South Korea, six closely located cement factories produce 31 million tons of cement annually. Their impact on the regional environment has been a public-policy issue, but their pollutants have not been continuously monitored nor have emissions inventories been fully verified. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…This can be explained by combined effect of the higher absolute uncertainty level due to low-quality clean pixel used for a SF correction, and generally low NO2 VCD leading to greater relative uncertainty per same absolute uncertainty. Still, both TROPOMI and HIS were able to capture some increased NO2 VCDs right above the cement kiln, which has been pointed as a major industrial point source of NO2 at the area (Kim et al, 2020). The research flight over the Pohang area further demonstrated the significance of NO2 emissions from the steel yards, since one of the world's largest steel yard is located within the city of Pohang (Fig.…”
Section: No2 Vcds In Three Industrial Areasmentioning
confidence: 92%
See 1 more Smart Citation
“…This can be explained by combined effect of the higher absolute uncertainty level due to low-quality clean pixel used for a SF correction, and generally low NO2 VCD leading to greater relative uncertainty per same absolute uncertainty. Still, both TROPOMI and HIS were able to capture some increased NO2 VCDs right above the cement kiln, which has been pointed as a major industrial point source of NO2 at the area (Kim et al, 2020). The research flight over the Pohang area further demonstrated the significance of NO2 emissions from the steel yards, since one of the world's largest steel yard is located within the city of Pohang (Fig.…”
Section: No2 Vcds In Three Industrial Areasmentioning
confidence: 92%
“…Three regions in Korea were selected as the target domain for the research flight: Chungnam, Jecheon, and Pohang. Each domain has one or more industrial point sources with substantial NO2 emissions (Choo et al, 2023;Kim et al, 2020;Cleansys, 2023), such as power plants, steel yards, petrochemical complexes, and cement kilns. generally displayed relatively low concentrations compared to the year-round average (Park et al, 2022), with the highest concentration observed at the southeastern side of the Seoul Metropolitan Area (SMA; 0.70 DU).…”
Section: Research Flightsmentioning
confidence: 99%
“…It is recommended to use it if the total input of chloride is higher than 0.3-0.4 kg of Cl/t of clinker. Nevertheless, the exact number depends on other factors too-especially sulfur volatility, tower cleaning tools, and the quality of their use-and in some cases, chloride inputs without operation of the bypass can be even higher [100].…”
Section: Proper Control Of Chloridesmentioning
confidence: 99%
“…The risk of cyclone blockage is increased in the case that this figure is higher than 3.5. In addition, maintaining high oxygen at the kiln inlet to decrease SO3 in the hot meal can minimize the risk of kiln stoppage due to cyclone blockage [100].…”
Section: Proper Control Of Chloridesmentioning
confidence: 99%
“…To reduce the severe NO x emission techniques, such as selective catalytic reduction (SCR) and selective non-catalytic reduction (SNCR) were developed. 7,8 Injection of higher values of urea can improve NO x reduction but may also increase ammonia slip. Reduction chemistry is a relatively simple chemical process.…”
Section: Introductionmentioning
confidence: 99%